Anti-nociceptive Potential of Olmuv™ and its Safety Study through Skin Irritation Test (Advancements in Homeopathic Research, 2022)
Introduction: Topical applications in the pain management play an important role. A formulation Olmuv™ developed with herbs used in homeopathy is targeted to treat pains of different origins. Though its ingredients are well-established traditionally as well as scientifically, there was no study conducted on this formulation. Hence this study was conducted with the objective to find out the anti-nociceptive effects and safety (skin irritation potential) of OlmuvTM. Materials and methods: Anti-nociceptive effect of Olmuv™ was conducted in Swiss albino mice. Animals were divided into 4 groups viz. vehicle control, disease control, standard therapy and treatment dose (6ml/kg). Pain was induced by the administration of carrageenan 0.1ml (1% solution) in paw joint region of animals. Eddy’s hot plate and tail flick method of hot water and cold-water assay were used to evaluate by the response time in seconds. Statistical analysis was accomplished using one-way analysis of variance (ANOVA) considering p value
Keywords: Olmuv™; skin irritation potential; anti-nociceptive effects; ANOVA